Biomarkers and Re–Os geochronology of solid bitumen in the Beiba Dome, northern Sichuan Basin, China: Implications for solid bitumen origin and petroleum system evolution. (April 2021) - Zhao, Bangsheng; Li, Rongxi; Qin, Xiaoli; Li, Delu; Wu, Xiaoli; Khaled, Ahmed; Zhou, Wei; Zhao, Di; Liu, Qi; Zhang, Yanni
Abstract: Solid bitumen is ubiquitous in the Sinian Dengying Formation dolomite, a crucial gas reservoir in the Sichuan Basin. We use biomarkers and Re–Os geochronology, coupled with burial-thermal evolution history to trace the source and formation timing of the solid bitumen, and to reconstruct the petroleum system evolution in the Dengying Formation of the Beiba Dome, northern Sichuan Basin. The bitumen reflectance (Rb) values of solid bitumen range from 1.92 to 3.95%, with the solid bitumen showing no fluorescence, indicating that the solid bitumen in the Dengying Formation dolomite has a high thermal maturity, which consequently belongs to pyrobitumen formed by thermal cracking of crude oil. The isoprenoids and terpanes indicate that the solid bitumen was sourced from a marine shale deposited under a reducing environment. The C27 –C29 regular sterane distribution of the solid bitumen is consistent with the Lower Cambrian Guojiaba Formation (Є1 g) organic-rich shale, indicating that the solid bitumen was derived from the Є1 g shale, rather than dolomite or shale within the Dengying Formation. The burial-thermal evolution history indicates that initial oil generation began in the Late Cambrian to the Early Silurian. Since the Early Permian, the Є1 g organic-rich shale re-entered the oil generation window, and formed a giant paleo-oil accumulation during the Late Triassic. Thermal cracking of crude oil occurred from the Late Triassic to the Early Cretaceous forming the extensive solid bitumen. The Re–Os isotopes of solid bitumen yield two similar isochron ages of 128.1 ± 7.3 Ma and 126.2 ± 8.0 Ma, which represents the timing of thermal cracking termination, i.e. the final timing of dry gas generation. This work highlights that the Re–Os geochronology has great potential to constrain the absolute timing of evolution of the petroleum system. Highlights: The solid bitumen belongs to pyrobitumen with a highly thermal maturity, formed by thermal cracking. The solid bitumen was derived from the Lower Cambrian Guojiaba Formation organic-rich shale. The solid bitumen was formed in the Early Cretaceous, which represents the timing of thermal cracking termination.